THE INTRODUCTION OF THE RAILWAY NETWORK INTO THE BUKHARA EMIRATE AND ITS ECONOMIC SIGNIFICANCE - Очилдиев Ф. Б. (TARIXIY TADQIQOTLAR, 2026)
The article analyzes the penetration of the Central Asian railway network into the territory of the Bukhara Emirate, the transformation of Bukhara and other cities into trade centers, and the interconnection of all settlements with one another. It examines the establishment of direct railway links between the cities of the emirate and the industrially developed cities of Central Asia and Russia. In addition, the study explores the volume of goods exported from the emirate to Russia via railway stations, the quantity of trade goods imported from Russia, and their impact on the development of trade and the economy between the two countries.